DOI: 10.33915/etd.2333
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particulate matter and hydrocarbon emissions from in-use heavy-duty diesel engines

Abstract: A continued increase in the use of diesel engines in light-duty and heavy-duty vehicles, and the uncertainties about the effects of their emissions on human health have focused attention on risk assessments of diesel engine exhaust. The characterization of diesel particulate matter (PM) and hydrocarbon (HC) emissions from in-use heavy-duty diesel engines and vehicles is the primary objective toward assessing potential health hazard with exposure to the diesel exhaust. The nature of particulate matter emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…In the open literature available to authors, using source signature for finding sources of exhaust particulate matter is quite established and were used as early as by Cadle et al . , Watson [26], and Bugarski . Maricq reviewed the chemical characterization of exhaust particulate matter and outlines the use of source signature for identifying the components of exhaust particulate matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the open literature available to authors, using source signature for finding sources of exhaust particulate matter is quite established and were used as early as by Cadle et al . , Watson [26], and Bugarski . Maricq reviewed the chemical characterization of exhaust particulate matter and outlines the use of source signature for identifying the components of exhaust particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…Source identification has been an established procedure in many society for automotive engineers (SAE) manuscripts, which is evident from their publicly available abstracts. In the open literature available to authors, using source signature for finding sources of exhaust particulate matter is quite established and were used as early as by Cadle et al [25], Watson [26], and Bugarski [27]. Maricq [28] reviewed the chemical characterization of exhaust particulate matter and outlines the use of source signature for identifying the components of exhaust particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dilution ratios is beyond the scope of this study. A comprehensive analysis of the theory and operation of this device can be found in Bugarski's (1999) study.…”
Section: System Modificationsmentioning
confidence: 99%
“…diesel engine equipped with a Cleaire ® DPF. Previous studies have reported PM mass concentration levels at or lower than 2007 standard levels can be achieved by running this engine with a DPF and ULSD fuel [138]. As a primary indirect injection engine, its relatively high NO x emission levels in raw exhaust make it easier to determine dilution ratios inside the primary tunnel by measuring NO x concentration levels.…”
Section: Engine and Test Cellmentioning
confidence: 99%